Analysis of corporate social responsibility, governance, and family ownership on firm value - Nela Marcelina Solin, Susi Dwi Mulyani, (Opción, 2019)
This study investigates the influence of corporate social responsibility (CSR), corporate governance (CG), and family ownership on firm value with profitability as moderating variable in the manufacturing companies that listed on Indonesia Stock Exchange period 2014-2016. The sampling technique is a purposive sampling method. The hypothesis test uses regression analysis. As a result, CG and profitability have a positive effect on firm value. CSR and family ownership are unable to effect on firm value. In conclusion, profitability as a moderating variable is unable to strengthen the effect of CSR, CG, and family ownership on firm value.